The Dynamics Of Reform Era Corruption In Indonesia Are Reviewed From Macroeconomic Analysis For 1999-2022 - Siti Nur Arofah; Hastarini Dwi Atmanti (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
This research aims to analyze the influence of economic growth, tax sector state revenue, Human Development Index, and poverty on the corruption perception index during the reform era in Indonesia from 1999 to 2022. Corruption can reduce the productivity of public spending, distort resource allocation, and slow down economic growth. This study uses multiple linear regression analysis tools on time series data from Indonesia for the years 1999-2022, with the dependent variable being the Corruption Perception Index (CPI), which reflects public perception of the quality of corruption in the country. A higher CPI index value indicates a lower level of corruption. The independent variables in this study are economic growth, tax sector revenue, HDI, and poverty. The research results show that simultaneously, the independent variables have a significant effect on the dependent variable, while partially, the economic growth and HDI variables have a significantly positive effect on the CPI, whereas the tax sector revenue variable has a significantly negative effect. However, the poverty variable has no significant effect on the CPI. The goodness of fit test results indicate that 95% of the influence of the independent variables on the dependent variable can be explained by the model, while 5% is explained by variables outside the model.